A Mentoring Leadership Skill Bagi Perangkat Desa dan Penggerak PKK, Desa Kemujan Kecamatan Karimunjawa - Santoso, Hero Budi; Noviarianto; Rahindra Bayu Kumara; Sri Tutie Rahayu; Prijantono Dillyanto; P. Tony. Kusumartono (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
Leadership is the main point of the development of an organization. Leadership is not only obtained from talent or charismatic nature, but can be obtained by mastering theoretical concepts and training in cultivating leadership. The availability of information, literacy and knowledge about the concept of leadership, as well as case studies of the implementation of leadership in organizations need to be improved, in order to foster a spirit of leadership and open up insight into leadership methods in organizational containers in Kemujang Village, Karimunjawa District, Kab. Jepara. The objectives of the community service activity to increasing knowledge about the principles of management and organizational leadership in Kemujang Village, increasing effectiveness in organizational management so that administrators are able to accommodate activities optimally and increase reference and literacy in the concept of organizational leadership and management. The methods used are presentations/lectures, discussions and case studies to discuss among the participants, as well as training in building leadership, organizational personality, understanding the roles, goals and functions of organizations and caring attitudes towards the community environment. The results of the basic leadership training services carried out by the service team can provide useful knowledge for participants who take part. So that it can be implemented in developing a qualified organization with various programs.